(untitled) (Revista Iberoamericana de Bioética, 2025)
Palliative care (PC) refers to an approach aimed at promoting quality of life and dignified care, emphasizing the inclusion of spirituality. However, integrating this dimension into PC has been a challenge for multidisciplinary teams. This study aimed to investigate professionals’ perceptions regarding the integration of spirituality, based on narrative bioethics (NBE). Semi-structured interviews were conducted and participants’ narratives were analyzed. The data revealed a vague definition of spirituality and its integration based on an “intuitive” perspective (respect); shared clinical conduct involves the patient’s contact with spirituality. It is concluded that teams need to refine and align their conceptions of spirituality, and the presence of a specialist in spiritual care (chaplain) on the team would make a significant contribution. Broader research may complement these perspectives.